ANOTHER LOOK AT COST OR MARKET WHICHEVER IS LOWER. - Husband, George R. (The Accounting Review, 1946)
The evaluation of inventories is of considerable importance for purposes of both the balance sheet and the income statement. In the former, the inventory evaluation influences the current-asset total, the grand total of all the assets, and the surplus figure; in the latter, the inventory evaluation materially influences the figures for cost of goods sold and for net profit. The general rule for purposes of balance-sheet evaluation is that assets should be exhibited at cost, whereas for purposes of the income statement the general rule has held that evaluations should be on such a basis that profits (and operating business losses) will be taken up only on the basis of sales. These rules are interrelated, as well as consistent with the concept of historical accounting. Departure from them represents a violation of realized, experiential accounting and must be Justified on other grounds. Notwithstanding these general rules it has long been. Considered good practice to evaluate the inventories on the basis of cost or market whichever is lower, thus frequently exhibiting the asset at less than cost.